Konsepsi Matakuliah Management dan Organisasi Paradigma Wahdahtul Ulum UIN Sumatera Utara - Suhairi, Suhairi; Ramadhani, Sri (JURNAL ADMINISTRASI KANTOR; Vol 10 No 2 (2022): Jurnal Administrasi Kantor (Desember 2022), 2023)
The purpose of this paper is to describe the trans-discipliner of the study of science management and the organization of secularity in the Islamic context, a policy of the State Islamic University of North Sumatra (Islamic Studies) the concept of integration of the unity of science paradigm wahdahtul ulum (WU) trans-discipliner the characterization of the Al-Quran and Hadits. In addition to the assumptions of unification of Islamic science learning in each major course (Management) the implications of theoretical definitions in the context of wahdatul ulum. The qualitative research methodology is in the form of reading sources for reviews of journals and literature reviews as relevant information material. The findings of a doctrine of secular-dichotomous sciences in Europe separated science and religion (double truth) truth. The author tries to describe the implications of Islamic Studies and the knowledge of Islamic Islamic Science as an introduction to management and organizational science courses. Keywords: Transdiscipliner, Management, Islam Studies, Wahdatul Ulum.